An invesigation of the physical and chemical changes occuring in a Fischer-Tropsch fixed bed catalyst during hydrocarbon synthesis - Duvenhage, Dawid Jakobus (My University, 1990)
Deactivation studies; making use of fixed bed reactors, wet chemical analysis, surface area, pore volume determinations and X-ray diffraction—, scanning electron microscope— and secondary ion mass spectrometry techniques; were performed on a low temperature iron Fischer—Tropsch catalyst. It was revealed that this catalyst is mainly deactivated by sulphur poisoning, oxidation of the catalytic reactive phases, sintering of the iron crystallites and to a lesser extent deactivation through fouling of the catalytic surface by carbonaceous deposits. It was found that the top entry section of the catalyst bed deactivated relatively fast, the bottom exit section also deactivated, but not as fast as the top section The central portion of the catalyst bed was least affected. Sulphur contaminants in the feed gas, even though present in only minute quantities, results in a loss of catalyst performance of the top section of the catalyst bed, while water, produced as a product from the Fischer—Tropsch reaction, oxidized and sintered the catalyst over the bottom section of the catalyst bed.
Thesis (M.Sc.)--University of the Witwatersrand, Faculty of Science (Chemistry), 1990
Keywords: Catalysis; Catalysts; Catalyst poisoning; Hydrocarbons